Structural Geology of the Škocjan Caves - Šebela, Stanka (Acta Carsologica, 2009)
The Škocjan Caves are developed inside 300 m thick column of Cretaceous and Paleocene limestones. Most of the underground Reka River flows within the 130 m thick Lipica Formation (K2 4-5). Data from field structural geological mapping (1:500) performed in 1991-1992 (Hankejev Kanal) and in 1997- 2007 (Tiha and Šumeča Jama) are analysed and presented on a new structural geological map. The Reka River follows bedding- plane strike and dip direction in Šumeča Jama and Hankejev Kanal. From the western part of Hankejev Kanal to the ponor in Martelova Dvorana the Reka River flows perpendicular to strike direction of bedding-planes with dip direction of the bedding contrary to river flow. Bedding planes with interbedded slips were especially favourable for the development of initial passages. The bend of the Reka River in Hankejev Kanal is developed at the intersection of multiple fault zones. Cross- Dinaric oriented faults in Podorna Dvorana and at northern edge of Martelova Dvorana can potentially be neotectonically active.